Treatment-Related Serious Adverse Events of Immune Checkpoint Inhibitors in Clinical Trials: A Systematic Review - Ouyang, Tao; Cao, Yanyan; Kan, Xuefeng; Chen, Lei; Ren, Yanqiao; Sun, Tao; Yan, Liangliang; Xiong, Bin; Liang, Bin; Zheng, Chuansheng (Frontiers in Oncology, 2021)
Background: Immune Checkpoint Inhibitors (ICIs) have been increasingly used in cancer therapy and produced unique toxicity profiles. This review aims to identify the patterns and incidence of treatment-related adverse events (trAEs) based on ICIs. Methods: PICOS/PRISMA methods were used to identify published English-language on PubMed, Web of Science and Scopus were searched from 2015 to 2020. Published clinical trials on ICI monotherapy single-agent ICIs, combined ICIs, and ICIs plus other treatment with tabulated data on grade≥3 trAEs were included. Odds ratio (OR), 2 tests were used to analyze for effect size and associations. Results: This review included 145 clinical trials involving 21786 patients. Grade 3-5 trAEs were more common with ICIs when they were plused with other treatments compared with ICI monotherapysingle-agent ICIs (54.3% versus 17.7%, 46.1%, p<0.05). Grade 3-5 trAEs were also more common with CTLA-4 mAbs compared with anti-PD-1 and anti-PD-L1 (34.2% versus 15.1%, 13.6%, p<0.05). Hyperthyroidism (OR 3.8, 95%CI 1.7–8.6), nausea (OR 3.7, 95%CI 2.5–5.3), diarrhea (OR 2.7, 95%CI 2.2–3.2), colitis (OR 3.4, 95%CI 2.7–4.3), ALT increase (OR 4.9, 95%CI 3.9–6.1), AST increase (OR 3.8, 95%CI 3.0–4.9), pruritus (OR 2.4, 95%CI 1.5–3.9), rash (OR 2.8, 95%CI 2.1–3.8), fatigue (OR 2.8, 95%CI 2.2–3.7), decreased appetite (OR 2.4, 95%CI 1.5–3.8), and hypophysitis (OR 2.0, 95%CI 1.2–3.3) were more frequent with combined ICIs. Diarrhea (OR 8.1, 95%CI 6.4–10.3), colitis (OR 12.2, 95%CI 8.7–17.1), ALT increase (OR 5.1, 95%CI 3.5–7.4), AST increase (OR 4.2, 95%CI 2.8–6.3), pruritus (OR 4.1, 95%CI 2.0–8.4), rash (OR 4.4, 95%CI 2.9–6.8), hypophysitis (OR 12.1, 95%CI 6.3–23.4) were more frequent with CTLA-4 mAbs; whereas pneumonitis (OR 4.7, 95% CI 2.1–10.3) were more common with PD-1 mAbs. Conclusions: Different immune checkpoint inhibitors appear to have varying treatment-related adverse events. A comprehensive summary of the incidences of treatment-related adverse events in clinical trials provides an important guide for clinicians.